Prototipo de mecanismo bicicleta electromecánica con corrector de postura cuatro barras para personas con discapacidad en extremidades inferiores. (2020)
The project presented was carried out due to the fact that there is a limitation of rehabilitation machines that allow the legs to be held in order to perform cyclic movements as a therapy method, since the current ones do not have leg braces for paraplegic patients. With the above, a proposal was achieved that innovates in the field of mechanics applied to health, since a prototype was designed and built coupled to a four-bar system mechanism to hold a patient's legs. With the development of the prototype, it allows to hold the legs, keeping a parallelism. Likewise, Mr. Absalon Garcia participated as a base for our research in the city of Neiva (Huila), from where the initial data was taken for the working measurements of the mechanism, dimension of the four-bar system, areas of subjection; as ergonomic support points for its later tests. A proposal was defined which took into account the following variables such as turning speed, torque, length of four-bar mechanism, geometries for four bars, engine power, transmission ratio, selection of materials, bicycle mechanism and a four-bar system used to correct the posture of the legs. Where it was achieved by means of an electromechanical mechanism to join a four-bar mechanism to a bicycle mechanism. Achieving as a result a practical functional prototype to perform a specific exercise such as cyclical movements.